Early Complications of Therapeutic Endoscopic Retrograde Cholangiopan Creatography: A Prospective Tertiary Hospital Study - Islam, MS; Alam, AHMT; Ahmed, SU; Zaman, KS; Islam, MN (Medicine Today, 2012)
DOI: http://dx.doi.org/10.3329/medtoday.v23i2.13096 Medicine TODAY Vol.23(2) 2011 pp.63-66